Synthesis and Characterization of Acridinium Dyes for Photoredox Catalysis - White, Alexander R.; Wang, Leifeng; Nicewicz, David A. (Synlett, 2019)
Photoredox catalysis is a rapidly evolving platform for synthetic methods development. The prominent use of acridinium salts as a sustainable option for photoredox catalysts has driven the development of more robust and synthetically useful versions based on this scaffold. However, more complicated syntheses, increased cost, and limited commercial availability have hindered the adoption of these catalysts by the greater synthetic community. By utilizing the direct conversion of a xanthylium salt into the corresponding acridinium as the key transformation, we present an efficient and scalable preparation of the most synthetically useful acridinium reported to date. This divergent strategy also enabled the preparation of a suite of novel acridinium dyes, allowing for a systematic investigation of substitution effects on their photophysical properties.
Keywords: photoredox; catalysis; synthesis; acridinium; organocatalyst